Kesiapan Regulasi Pemerintah dalam Implementasi Kerjasama Pemerintah dengan Badan Usaha untuk Penyediaan Infrastruktur Metropolitan Rebana - Widya Nissa Wildani; Asnita Frida Sebayang (Bandung Conference Series: Economics Studies, 2023)
Abstract Rebana Metropolitan Area is projected to become an integrated industrial area through the development of urban-rural industrial area connectivity to improve better socio-economic conditions. There will be 81 priority projects for Metropolitan Rebana development, to realize this development alternative non-APBN financing is needed. One of the financing alternatives is PPP, seeing that there is a gap between the availability of the government sector's budget and the number of projects that must be realized. Implementing the PPP financing scheme, requires readiness from the government sector, especially readiness in regulations. Regulation is an important matter, as the basis for PPP implementation must be considered in detail and the need for conformity with development needs to attract investors to contribute to the provision of national infrastructure through the PPP scheme. This study uses the Community Readiness Model (CRM) from (Tri-Ethnic for Prevention Research). Furthermore, using SWOT to find out the strategy for successful PPP implementation in the Metropolitan Rebana infrastructure project. The results of the study show that the readiness level of the readiness stage is at the initiation stage with a score of 6.2. This stage means that the government sector has prepared and allocated and implemented things for the successful implementation of the PPP scheme, and the SWOT strategy shows the result that internal factors and external factors of strengths (S) and opportunities (O) have a higher score or value compared to weakness (W) and threat (T) factors. Abstrak Wilayah Metropolitan Rebana yang diproyeksikan menjadi kawasan industri terintegrasi melalui pengembangan konektivitas kawasan industri perkotaan-perdesaan untuk meningkatkan kondisi sosial-ekonomi yang lebih baik. Pembangunan Metropolitan Rebana akan terdapat 81 proyek prioritas, tentunya untuk mewujudkan pembangunan tersebut diperlukannya alternatif pembiayaan non APBN. Salah satu alternatif pembiayaan adalah KPBU, melihat terdapat gap antara ketersediaan anggaran yang dimiliki sektor pemerintah dengan banyaknya proyek yang harus direalisasikan. Dalam mengimplementasikan skema pembiayaan KPBU diperlukannya kesiapa dari sektor pemerintah, terutama kesiapan dalam regulasi. Regulasi merupakan hal penting, sebagai dasar dari pelaksanaan KPBU yang harus diperhatikan secara mendetail dan perlunya kesesuaian dengan kebutuhan pembangunan untuk menarik minat investor agar berkontribusi dalam penyediaan infrastruktur nasional melalui skema KPBU. Penelitian ini menggunakan Community Readiness Model (CRM) dari (Tri-Ethnic for Prevention Research). Selanjutnya, menggunakan SWOT untuk mengetahui strategi keberhasilan implementasi KPBU pada proyek infrastruktur Metropolitan Rebana. Hasil penelitian menunjukan tingkat kesiapan readiness stage berada pada tahap initiation dengan skor 6,2. Tahapan ini mengartikan bahwa sektor pemerintah sudah mempersipakan dan mengalokasikan dan melaksanakan sesuatu hal untuk keberhasilan impelemtasi skema KPBU, serta strategi SWOT menunjukan hasil bahwa faktor internal dan faktor eksternal dari kekuatan (S) dan peluang (O) memiliki skor atau nilai yang lebih tinggi dibandingkan dengan faktor kelemahan (W) dan ancaman (T).